Hak Untuk Bersuara, Kewajiban Untuk Berpartisipasi: Makna Demokrasi Sesungguhnya - Lestari Purnama Intan Gulo; Elrica April Yanti Mendrofa (Jurnal Ilmu Pendidikan Pancasila, Kewarganegaraan, dan Hukum, 2025)
In a democratic system, every individual has the right to voice their opinions and ideas, which become the foundation for the formation of public policies that are fair and in favor of the common interest. However, this right is also accompanied by the obligation to actively participate in democratic processes, whether in elections, public discussion forums, or in running the government. Democracy is not only about freedom of speech, but also about active contribution in determining the direction of the nation. This article examines the relationship between individual and collective rights and obligations in realizing quality democracy, as well as the challenges faced by society in implementing both. This discussion aims to strengthen the understanding that democracy is achieved when every citizen not only knows his or her true rights, but also carries out his or her obligation to participate in the political process constructively.